The Effect of Childbirth Planning and Complication Prevention Program Education on the Knowledge and Attitudes of Pregnant Women - Chintia Kartikaningtias; Luluk Nur Aini; Nanik Susanti (Program Studi Sarjana Kesehatan Masyarakat Universitas Prima Indonesia, 2025)
The high maternal mortality rate (MMR) and infant mortality rate (IMR) are the main drivers for the implementation of the Childbirth Planning and Complication Prevention Program (P4K). The P4K program plays an essential role in helping pregnant women prepare for labor and detect potential complications. The success of this program is highly dependent on the knowledge and attitude of pregnant women towards childbirth planning and the complication prevention program itself. The purpose of this study was to determine the Education of childbirth planning programs and prevention of complications on the knowledge and attitudes of pregnant women. The research design used was a quasi-experiment with a one-group pretest-posttest design. The research was conducted at the Praktik Mandiri Bidan of Parangargo Village, Wagir District, Malang Regency in April 2024. The subjects of this study were all pregnant women who underwent antenatal care examination, a many of 30 people, with a purposive sampling technique. Data collection was done by distributing questionnaires to pregnant women. The intervention was provided in the form of a childbirth planning and complication prevention program to measure the knowledge and attitudes of pregnant women before and after the intervention. Analysis of research data using the Wilcoxon test. The results showed that there was an effect of providing the P4K program on increasing the knowledge and attitudes of pregnant women through the P4K program.